2014
DOI: 10.3390/bios4020137
|View full text |Cite
|
Sign up to set email alerts
|

A Phage Display Screening Derived Peptide with Affinity for the Adeninyl Moiety

Abstract: Phage display screening of a surface-immobilized adenine derivative led to the identification of a heptameric peptide with selectivity for adenine as demonstrated through quartz crystal microbalance (QCM) studies. The peptide demonstrated a concentration dependent affinity for an adeninyl moiety decorated surface (KD of 968 ± 53.3 μM), which highlights the power of piezoelectric sensing in the study of weak interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Here, we notice that this peak increases in intensity and undergoes a red shift (from 1575 to 1570 cm ) when DNA is absorbed on HNs. A red shift of this mode was also observed by Elmlund et al [ 41 ] for Adenine absorbed onto quartz surface. Therefore, the shift of asymmetric stretching from 1242 cm (observed in dehydrated DNA with both far-field and nano-FTIR spectroscopy) to 1253 cm (in DNA–HNs), together with the strong intensity reduction of the 1698 cm peak (associated to thymine C2=O2 moiety) and the intensity increase of the peak at 1570 cm (linked to Adenine N-H) in DNA–HNs spectra, point towards the occurrence of both base-specific and backbone structural variations of DNA when adsorbed on HNs.…”
Section: Resultssupporting
confidence: 80%
“…Here, we notice that this peak increases in intensity and undergoes a red shift (from 1575 to 1570 cm ) when DNA is absorbed on HNs. A red shift of this mode was also observed by Elmlund et al [ 41 ] for Adenine absorbed onto quartz surface. Therefore, the shift of asymmetric stretching from 1242 cm (observed in dehydrated DNA with both far-field and nano-FTIR spectroscopy) to 1253 cm (in DNA–HNs), together with the strong intensity reduction of the 1698 cm peak (associated to thymine C2=O2 moiety) and the intensity increase of the peak at 1570 cm (linked to Adenine N-H) in DNA–HNs spectra, point towards the occurrence of both base-specific and backbone structural variations of DNA when adsorbed on HNs.…”
Section: Resultssupporting
confidence: 80%
“…A comparison of this study with previously reported works is presented in Table S1 (Supporting Information). Furthermore, the values of the association constant ( K a ) and disassociation constant ( K d ) for the BSA/Ab/PANnf/ITO immunoelectrode were estimated with the Hanes–Wolf plot [graph between the antigen concentration and the antigen concentration divided by the current, Figure A(c)]. The inverse value of the slope observed by the linear fitting of the Hanes–Wolf plot gave a value of K a of 45.2 ng/mL, whereas the product of the K a and intercept gave a value of K d of 8 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The value of low detection limit calculated using formula 3σ b /m criteria, where m is the slope of the calibration graph and σ b is the standard deviation of the blank signal. Furthermore, the value of association (K a ) for the BSA/Ab/ZnO/ITO immunoelectrode is estimated using the Hanes-Wolf plot 37,41 (graph between [antigen concentrations] and [antigen concentration/current]) as shown in Fig. 5C.…”
Section: Electrochemical Studies-optimization Of Electrochemicalmentioning
confidence: 99%